Organização do espaço rural de Pinhal Grande - RS: potencialidades e desafios da agricultura familiar - Dallanôra, Ivani Belenice (2018)
This research has its relevance once it analyzes the organization of the activities developed in the rural area, its modernization process and the reflexes of rural spatial organization in the productive dynamics of family agriculture as well as in the socioeconomic conditions of the population. Its general objective is to analyze the process of organization and/or reorganization of the rural area of Pinhal Grande, as well as to identify the potentialities and challenges of family agriculture in the municipality, in the time scale from 1993 to 2017. Specifically, it was intended to) evaluate the spatial, technical and socioeconomic transformations that occurred in the rural area of the municipality from 1993 to 2017; (b) to spatialize, by regionalization process, the productive matrix of the rural space, relating its organization to the development of family properties; (c) to identify the participation of family agriculture in the development of the local/regional economy, knowing the productive potential offered by family farms and the challenges encountered to develop; (d) to identify the causes responsible for the migratory processes of this area of study and to know the public policies aimed at the development of the rural space and the socio-spatial organization of family agriculture. This research was developed based on the criteria used to identify its importance in the scientific production process. Therefore, it is classified as a descriptive, data collection, laboratory and bibliographic research. Firstly, the theoretical framework was elaborated to learn about the subject to be analyzed. In a second moment, the data were collected together with the Brazilian Institute of Geography and Statistics (IBGE) referring to the 1995, 2006, and 1993, 1998, 2003, 2011 and 2015 agricultural and livestock census, with the objective of analyzing the organization of the (FEPAGRO), the Special Secretariat for Family Agriculture and Agrarian Development (SEAD), and the Central Bank of Brazil, in order to identify the responsible public policies development of family properties. In a third moment, interviews with representatives of public bodies (EMATER, Rural Workers' Union and Municipal Secretariat of Agriculture, Industry and Commerce) were carried out to identify the contribution of these bodies in the process of diversification and development of productive activities in rural areas. Finally, the research instrument was applied through questionnaires, containing open and closed questions addressed to family farmers, in order to verify the current organization of the rural area of the municipality and the potentialities and challenges of family agriculture. Once the research was carried out, the data collected were analyzed, and these were disseminated through textual production, including graphics, tables, maps and photos. In this context, it can be concluded that the family agriculture of Pinhal Grande presents itself in a contradictory way, marked by dynamic spaces where commercial crops predominate, such as soybeans and productive potential that, through the introduction of new activities, diversify production, adding income and boosting the family ownership. On the other hand, it is possible to visualize a family agriculture dependent on the production of traditional products (tobacco, corn and beans) that currently "tries" to keep the family farmer in the rural space.